1986
DOI: 10.1055/s-2007-969352
|View full text |Cite
|
Sign up to set email alerts
|

The Examining of Isolated Tannins and their Astringent Effect

Abstract: PosterIn conclusion, these results clearly show the importance of the substituents on the flavonoid-structure. Methylation of the 3-hydroxyfunction greatly enhances the antiviral properties, but does not change cardio-vascular activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Preliminary phytochemical analysis revealed that the leaf extract of S. jollyanum contains alkaloids, tannins, saponins, flavonoids and cardiac glycosides. These plant phytochemicals play important preventive activities mainly as anticancer, antidiarrheals, antioxidant, anti-parasitic, antiviral, antidiabetic, antibacterial, anti-inflammatory, antimicrobial, anti-aging, antidepressant, and wound healing (Athanasiadou et al, 2001;Grujić-Vasić et al, 1986;Kang et al, 2011;Bahramsoltani et al, 2014). It is also reported that leaves containing these phytochemicals help in hypocholesterolemic, immunostimulant, and anticarcinogenic properties and are believed to lower the risk of cancer and other chronic diseases in humans (Ros, 2000;Hostanska et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary phytochemical analysis revealed that the leaf extract of S. jollyanum contains alkaloids, tannins, saponins, flavonoids and cardiac glycosides. These plant phytochemicals play important preventive activities mainly as anticancer, antidiarrheals, antioxidant, anti-parasitic, antiviral, antidiabetic, antibacterial, anti-inflammatory, antimicrobial, anti-aging, antidepressant, and wound healing (Athanasiadou et al, 2001;Grujić-Vasić et al, 1986;Kang et al, 2011;Bahramsoltani et al, 2014). It is also reported that leaves containing these phytochemicals help in hypocholesterolemic, immunostimulant, and anticarcinogenic properties and are believed to lower the risk of cancer and other chronic diseases in humans (Ros, 2000;Hostanska et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…20 Gelatin tannate is commonly employed as an intestinal astringent and present in the market with various names, such as tanagel, gelenterum, or tasectan. 21 This complex passes through the stomach unaltered to dissolve into gelatine and tannic acid once in the gut, where it may exert its action by restoring the physiological function of the intestine. Furthermore, the well-known astringent properties of tannins allow the precipitation of proinflammatory mucoproteins from the intestinal mucus and their elimination through the faeces.…”
Section: Introductionmentioning
confidence: 99%